Occupational health services in selected International Commission on Occupational Health (ICOH) member countries - Jorma Rantanen; Suvi Lehtinen; Sergio Iavicoli (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVES: International organizations have encouraged countries to organize occupational health services (OHS) for all working people. This study surveyed how that objective has been achieved in a sample of International Commission on Occupational Health (ICOH) member countries from all continents. METHOD: A structured questionnaire was sent to ICOH national secretaries in 61 countries. The survey focused on (i) policies and strategies; (ii) systems, institutions, and infrastructures; (iii) contents and activities; (iv) human and other resources; (v) financing; and (v) future priorities in the development of national OHS systems. RESULTS: Of 47 respondents, 70% had drawn up a policy and strategy for OHS and 79% had a national institute of occupational health or safety. The calculated coverage of workers was 19% among the respondent countries. Sixty percent of respondent countries used multiple channels for service provision and 70% provided mixed contents of OHS with preventive and curative services. Almost all (94%) reported availability of multidisciplinary experts, but not in sufficient numbers. OHS is financed through combined employer plus insurance financing in 62% of respondents and through employer financing only in 38%. The countries identified well the needs for future development of OHS. CONCLUSIONS: In spite of documented policies for OHS, only slightly over one third of the surveyed countries had organized OHS for more than 50% of workers. The vast majority of workers of the world are underserved due to four gaps in OHS: implementation, coverage, content, and capacity.